2007
DOI: 10.1017/s0021932007001836
|View full text |Cite
|
Sign up to set email alerts
|

Physical Spousal Violence Against Women in India: Some Risk Factors

Abstract: Domestic spousal violence against women in developing countries like India, is now beginning to be recognized as a widespread health problem impeding development. This study aimed to explore the risk and protective factors for lifetime spousal physical violence. A cross-sectional household survey was carried out in rural, urban and urban-slum areas across seven sites in India, among women aged 15-49 years, living with a child less than 18 years of age. The sample was selected using the probability proportionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
180
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 10 publications
15
180
0
1
Order By: Relevance
“…Although a large and growing literature exists on the correlates of spousal violence, a complete picture of the risk factor for violence is yet to emerge. Several variables have been linked with spousal violence, among which are women's education and husband's/partner's education [9][10][11][12], wealth [13][14][15], use of alcohol [16,17], attitudes to violence [18], and women having a say regarding decision about their health care by the woman [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although a large and growing literature exists on the correlates of spousal violence, a complete picture of the risk factor for violence is yet to emerge. Several variables have been linked with spousal violence, among which are women's education and husband's/partner's education [9][10][11][12], wealth [13][14][15], use of alcohol [16,17], attitudes to violence [18], and women having a say regarding decision about their health care by the woman [19].…”
Section: Introductionmentioning
confidence: 99%
“…The association of family income and IPV was found to be highly significant in other studies conducted in India. 9,13 There was significant association between the type of marriage and IPV. In this study the arranged marriage was found to be protective when compared with IPV in love marriage.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8][9] Employed women have been found to report violence more frequently than unemployed women in a number of other studies. [11][12][13] There are still grey areas in the understanding of IPV, its various forms and different factors bearing influence on it. Through this study we attempt to estimate the proportion of Group -D married women experiencing IPV and assess their influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The association of family income and GBV was found to be highly significant in other studies conducted in India. 15,17 GBV has severe reproductive health impacts, including gynecological problems, unintended pregnancies, and perhaps most gravely, increased risk of maternal mortality and STIs, including HIV. Studies show that physical abuse occurs at some point during approximately 4 percent to 15 percent of pregnancies in countries as varied as the United States, Canada, Sweden, the United Kingdom, and South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Employed women have been found to report violence more frequently than unemployed women in a number of other studies. 16,17 There are still grey areas in the understanding of GBV, its various forms and different risk factors behind it. Through this study we attempt to estimate the proportion of knowledge of Group -D workers among hospitals of NCT (National Capital Territory), Delhi regarding awareness about GBV and the risk factors to become GBV victims.…”
Section: Introductionmentioning
confidence: 99%